Relevance theory and the social realities of communication - Johnson, Marilynn (Frontiers in Psychology, 2024)
A central tenet of theories of meaning in the Gricean tradition—such as Relevance Theory—is that others will come to believe certain things simply by recognizing our intentions to communicate. In this article I demonstrate that this is not equally the case for all interlocutors; some bear additional burdens. In particular, I argue that this can happen in two ways. First, I demonstrate how a response to persistent testimonial injustice can be understood in terms of Sperber and Wilson’s 2015 distinction between meaning-that and showing-that; a speaker who experiences repeated testimonial injustice will often move down the meaning vs. showing continuum. This is a result of a speaker learning that recognition of her intention has not in her experience been sufficient to induce the intended response in the hearer. Secondly, in consideration of social science research around perception of accent prestige and other status cues, I detail further costs borne by those who change their physical appearance and voice to be perceived as more credible. The costs of communication are not equal for all: they are greater for those who face a credibility deficit based in identity prejudice. Overall, by bringing Fricker’s notion of testimonial injustice to bear on Relevance Theory, this article shows how social factors affect the reality of how interlocutors communicate.